1993
DOI: 10.1093/bja/70.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac and Ketoprofen for Pain Treatment After Elective Casesarean Section

Abstract: We have studied the effect of a constant infusion of diclofenac 150 mg/24 h, ketoprofen 200 mg/24 h or placebo on postoperative pain after elective Caesarean section performed under spinal or extradural block in 90 patients in a prospective, randomized and double-blind study. During the first 24 h after operation, patients in the treatment groups were more comfortable than the placebo group (P < 0.005); the diclofenac group needed a mean of oxycodone 21.6 mg/24 h and the ketoprofen group 21.2 mg/24 h, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…The doses of diclofenac and ketoprofen in the present study were choosen according to the recommended maximum doses; these doses showed to be equianalgesic also in a previous clinical study [15]. The following considerations led us to use the 3 dosages employed in our study: (1) Small doses of NSAIDs (subdose 1) inhibit the synthesis ofthromboxane A2 but do not interfere with the action of other enzymes, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…The doses of diclofenac and ketoprofen in the present study were choosen according to the recommended maximum doses; these doses showed to be equianalgesic also in a previous clinical study [15]. The following considerations led us to use the 3 dosages employed in our study: (1) Small doses of NSAIDs (subdose 1) inhibit the synthesis ofthromboxane A2 but do not interfere with the action of other enzymes, e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that the analgesic efficacy of NSAIDs could reduce opioid consumption after Cesarean delivery. [17][18][19] However, wound pain and uterine contraction pain are qualitatively different. Our study demonstrates that the analgesic effect of iv tenoxicam can reduce the intensity of postpartum uterine contraction pain.…”
Section: Objectif : La Douleur Des Contractions Utérines Du Postpartumentioning
confidence: 99%
“…20,21 Reports have shown the analgesic effect of iv ketoprofen and diclofenac for the treatment of pain after Cesarean delivery. 17 However, the half-life of ketoprofen is five to six hours and that of diclofenac is 1.5 hr, 22 indicating that repeated doses may be needed. Tenoxicam specifically inhibits prostaglandin synthetase and has a long plasma half-life (75 hr) allowing once daily dosage.…”
Section: Objectif : La Douleur Des Contractions Utérines Du Postpartumentioning
confidence: 99%
“…So it is not always applicable or without side effect and require skill manpower. Now a days another combined analgesic method, opioid with NSAIDs is used to manage postoperative pain 9 with the aim of reduction of opioid doses. 8 Combined analgesic techniques are also popular for postoperative pain management in this country without definitive effective method of drugs administration.…”
mentioning
confidence: 99%
“…In our setting among the NSAIDs diclofenac sodium is commonly used, easily available and very cheap and equianlgesic with ketoprofen, ketorolac and piroxicam 9,10 . Among the opioids pethidine is one which is supplied to the Government hospital though not easily procurable from the open market.…”
mentioning
confidence: 99%